1. The problem statement, all variables and given/known data dy/dx=ky(1-y/M) where p is smaller than m and k is positive 3. The attempt at a solution ∫dy/(ky(1-y/M))=x ∫dy/(ky(1-y/M))=∫(a/ky + b/(1-y/M))dy then i introduced 2 new variables (a and b) multiplied them out so that 1/(ky(1-y/M))=(a(1-y/M)+bky)/(ky(1-y/M)) cancelled out the lower half and you have 1=a(1-y/M)+bky then i get a little stuck, im not even sure you can say that with the A and B becuase when you have 1/(x+2)^2 it equals a/(x+2)+b/(x+2)^2. so yes. help?